1996
DOI: 10.1002/hlca.19960790705
|View full text |Cite
|
Sign up to set email alerts
|

The Degradation Mechanism of an Oral Cephalosporin: Cefaclor

Abstract: The degradation of cefaclor (l), an oral cephalosporin antibiotic, was studied at 37O in a neutral aqueous medium by HPLC and 'H-NMR. Under these conditions, 1 underwent intramolecular aminolysis by the 7-sidechain NH, group on the 8-lactam moiety to give a piperazine-2,s-dione. The most prominent peak in the HPLC profile of a degradation solution from 1 was isolated by prep. HPLC. Mechanistically, the formation of this degradation product cis-11 from 1 involves the contraction from a six-membered cephem ring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The degradation pathways of cefaclor under neutral and basic pH conditions are complex, essentially unexplored, and remain to be elucidated. The recent study by Vilanova et al 24 describing a major pathway of cefaclor degradation under neutral conditions provides an excellent start to exploring these degradation pathways. The major solid-state degradation pathways described by Dorman et al 21 lead to multiple degradation products, many of which are not formed under aqueous conditions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The degradation pathways of cefaclor under neutral and basic pH conditions are complex, essentially unexplored, and remain to be elucidated. The recent study by Vilanova et al 24 describing a major pathway of cefaclor degradation under neutral conditions provides an excellent start to exploring these degradation pathways. The major solid-state degradation pathways described by Dorman et al 21 lead to multiple degradation products, many of which are not formed under aqueous conditions.…”
Section: Discussionmentioning
confidence: 98%
“…In a more recent study of the neutral aqueous degradation of cefaclor, Vilanova et al 24 provided structural evidence for this intramolecular cyclization pathway. Under acidic conditions, however, the nitrogen would be protonated, significantly reducing nucleophilicity.…”
Section: Scheme 2spathway A: Formation Of Thiazolesmentioning
confidence: 95%
“…19 We found that the ring‐opened products showed the expected diagnostic shift in absorbance due to piperazinedione formation,19a and, in contrast to intact cefaclor, no longer showed any spectral change upon treatment with NDM‐1, as would be expected for products that lack a β‐lactam bond. We did not further purify each component from the resulting mixture, due to the well‐documented instability of the degradation products of cefaclor and related cephems,19c, d and we used the mixture for inactivation tests.…”
Section: Resultsmentioning
confidence: 99%
“…Electrospray ionization mass spectrometry, usually coupled with high‐performance liquid chromatography (HPLC/ESI‐MS), has been successfully applied to their analysis . However, there is little nuclear magnetic resonance (NMR) data reported concerning the products of their hydrolysis and, to the best of our knowledge, there is no ESI‐MS data reported concerning the products. It is reasonable to expect that the products of cephalosporin hydrolysis are unstable and undergo further transformation (e.g.…”
Section: Introductionmentioning
confidence: 99%